HUBUNGAN ANTARA LAFAL, KONTEKS, DAN MAKNA DALAM AL-QUR`AN - Sukamta, Sukamta (Adabiyyāt: Jurnal Bahasa dan Sastra, 2017)
This article presents the results of research on the relationship between pronunciation, context, and meaning in the Qur`an. With the neuroscience approach, naḥw, and ilm al-dalālah, the discussion focused on six things: the selection of the form of the word (sīgah), the mention or disposal of the letters tā or yā, the use of the form mufrad or muṡanna, the choice of wazn, the use of long vowel marks (madd), harakat ḍammah or tasydīd, and selection of certain words. The method used is comparing various verses that contain words or phrases with the same linguistic problems, analyzing their meanings to conclude the results. The analysis of the intended meaning is carried out through a search for the context of each, by considering the differences in the pronunciation of each sound. This research shows that in the Qur`an, the use of pronunciation is very suitable with the meaning in question and the context behind it.